‘Learning walks’: Dialogic spaces for integrating theory and practice in a renewed BEd foundation phase curriculum - Zinn, Denise; Geduld, Deidre; Delport, Aletta; Jordaan, Christina (South African journal of childhood education, 2014)
In teacher education, the integration of theory and practice is perhaps best manifested in work-integrated learning (WiL), which entails the merging of academic and professional knowledge domains (CHE 2011). The redesign of current BEd programmes at Nelson Mandela Metropolitan University (NMMU) to align with the Faculty of Education’s new vision and mission started in 2011. Rigorous interrogation of previous and current paradigms and practices led to uncomfortable awareness of the lack of relevance of teacher preparation programmes in relation to conditions in the majority of schools in the country. Furthermore, the undesired schism between theory and practice was clearly exacerbated by the existing teaching practice model. The primary challenge was to design integrated, coherent new BEd programmes, to be responsive to the realities of the majority of South African schools, and to facilitate the connection between theory and practice in the teacher education programme. The study described in this article responded to this challenge through the application of a humanising curriculum framework that had been co-constructed within the Faculty. It led to the implementation of ‘learning walks’, the name given to the dialogic spaces which were created to develop and inform a new model of WiL.